2017
DOI: 10.1177/1403494817729921
|View full text |Cite
|
Sign up to set email alerts
|

Public health terminology: Hindrance to a Health in All Policies approach?

Abstract: This paper promotes debate about the appropriateness of using the terms 'public health' and 'public health work' at the local level. It suggests that adaptation is suitable and necessary, unless it compromises knowledge, responsibility and a systematic approach. This study concludes that the use of terminology is a central factor when implementing the Norwegian Public Health Act at the local level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…As such, the SDH might be more efficiently addressed by means of sectoral action in various non-health sectors, emphasizing equity rather than health. This may find support in the studies by Scheele et al 4 and Synnevåg et al 13 who found that an emphasis on “social sustainability” or “living conditions” may function better to establish support across government sectors. Thus, if the aim is a fair distribution of social and economic resources between social groups in general policy-making, it might be time to stop framing the conversation to be focused on health.…”
Section: Time To Ditch the H Word?mentioning
confidence: 82%
See 1 more Smart Citation
“…As such, the SDH might be more efficiently addressed by means of sectoral action in various non-health sectors, emphasizing equity rather than health. This may find support in the studies by Scheele et al 4 and Synnevåg et al 13 who found that an emphasis on “social sustainability” or “living conditions” may function better to establish support across government sectors. Thus, if the aim is a fair distribution of social and economic resources between social groups in general policy-making, it might be time to stop framing the conversation to be focused on health.…”
Section: Time To Ditch the H Word?mentioning
confidence: 82%
“…When considering how this may affect the public health coordinators’ ability to effect change, a study among municipalities implementing the Norwegian Public Health Act is interesting. Synnevåg et al 13 reported how several informants in Norwegian municipalities found it inappropriate for public health to take ownership of sectoral operations, as practitioners already carried out the kind of work referred to with the public health terminology in their daily operations as teachers, social workers, and urban planners, “thus questioning the need to call it public health work” (p. 70). Consequently, Synnevåg and colleagues cautioned the risk of health imperialism if all local policy-making is labelled to be a matter of health.…”
Section: The Theory Of Change Of Hiapmentioning
confidence: 99%
“…Inspired by new institutionalism, we regard organisations and their agents to be dependent on their institutional environment and on gaining legitimacy not only to succeed economically but also to survive [8][9][10]. To examine HiAP, other scholars have used institutional perspectives, such as path dependency and rationalised myth [11][12], institutional logics [13] and translation of organisational ideas [14][15]. By contrast, studies that apply a legitimacy perspective have been difficult to find.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…In comparison, no one in municipalities 1 and 2 did. Consequently, living conditions were also used together with the terms public health and public health work in their planning documents [15]. When asked if public health is a central area of interest amongst the politicians, one informant said the following:…”
Section: Cognitive Legitimacymentioning
confidence: 99%
“…Due to its technical/political duality, HiAP carries an inevitable level of vagueness, and its meaning requires contextual adaptation. With the recognition that all policy areas impact on health, HiAP opens up a terminological 'Pandora's box' of what qualifies as public health promotion, and whether 'health' remains an appropriate term when used in such an all-encompassing way (Synnevåg et al, 2018). Such use of language runs the risk of being perceived as 'health imperialistic' (Banken, 2001;Kemm, 2001).…”
mentioning
confidence: 99%